The Size of Political Jurisdictions: Evidence from a Fascist Consolidation - Guido de Blasio; Alberto Dalmazzo; Monica Andini (European Regional Science Association (ERSA), 2013)
The paper uses the consolidation of municipalities brought about by the Fascist dictatorship in Italy during the 1920s to gauge the role of the size of local jurisdictions for economic development. It finds that the consolidation was associated with relevant net welfare gains for the communities involved. In particular, the advantages related to the bigger economies of scale made possible in jurisdictions of larger size overwhelmed the costs owing to the higher heterogeneity.
Keywords: 330; city size; local government; local economic development